E-Government Implementation in Urban Parking Management: A Study of the Palembang Parking Information Application System (SIAPP) - Maharani, Maharani; Puji Lestari, Delfiazi; Uswatun Hasanah, Ade; Halbadika Fahlevi, Arry; Paradila, Suci (Asosiasi Ilmuwan Administrasi Negara (AsIAN), 2025)
This study examines the implementation of the Palembang Parking Information Application System (SIAPP) as an e-Government initiative in urban parking services. Existing research on digital and smart parking systems has largely focused on their technical design and performance, with limited insight into how they are implemented and maintained within local government institutions. To address this gap, this study analyzes the institutional, organizational, and managerial factors that shape SIAPP's effectiveness. A qualitative descriptive approach was employed, using in-depth interviews, field observations, and document analysis to capture the dynamics of implementation in practice. The findings indicate that SIAPP has facilitated a shift from manual to ICT-based parking management, thereby improving operational efficiency, transparency, and accountability, and increasing local government revenue. Digital record-keeping and information accessibility have strengthened oversight and helped reduce illegal parking practices. However, the results also reveal uneven implementation outcomes. Institutional and policy support emerged as key enabling factors, while limited human resource capacity and the continuation of partially manual administrative processes limited the system's performance despite adequate technological infrastructure. The study further demonstrates that SIAPP generates value for both the government and citizens, particularly through improved revenue control and increased service trust. These findings underscore that effective e-Government implementation in urban services depends not only on technological readiness but also on sustained institutional commitment, capacity building, inter-agency data integration, and public engagement, which offer relevant policy insights for urban digital governance.